Curvature analysis for composite with orthogonal, asymmetrical multi‐layer structure - Šliseris, Jānis; Rocēns, Kārlis (Journal of Civil Engineering and Management, 2010)
An option for reducing material consumption in bent construction is flat plate replacement with a curved or saddle shaped plate (shell). This option applies to plywood sheet, provided that the curved or saddle shaped plates are made in widely used multilevel plywood presses with parallel shelves using layers with an appropriate physical properties, geometric dimensions and orientation, creating a structurally asymmetrical sheet, relative to mid‐surface. Improved currently used method for calculation of curvature with taking into account curvature interaction effect and elastic characteristic change in moisture changing process. Compared results obtained by improved method and finite element method. Using improved method calculated values of curvature for a sheet with different geometrical properties and moisture conditions. First Published Online: 24 Jun 2011